Theorethical Review: Financial Management in The Agribusiness Sector and That Implications for Economic Growth - Sheyoputri, Aylee Christine Alamsyah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study conducts a comprehensive systematic literature review to evaluate the evolution and current state of financial management within the agribusiness sector, focusing on the impact of digital transformation and collaborative financial strategies on economic growth and sustainability. Utilizing VOSviewer for bibliometric visualization and analysis, this research synthesizes findings from over 200 peer-reviewed articles indexed in the Scopus database from the past decade. The articles were selected based on their relevance to financial management practices, digital innovation, and sustainable agricultural strategies. The research methodology involved a meticulous selection process to ensure that only articles that met strict criteria on relevance, timeliness, and academic rigor were included. This enabled the identification of emerging themes and critical intersections between financial management and technological advancement in agribusiness. The findings reveal that effective financial management significantly influences the economic outcomes and sustainability of agribusiness enterprises. Networking and collaborative financial strategies, supported by digital innovations such as precision agriculture and blockchain technology, are identified as key drivers for enhancing productivity and sustainability. The results also underscore the critical role of integrating financial management training in agricultural education programs to equip future professionals with the necessary skills for economic growth. This research highlights the necessity of strategic financial management in fostering sustainable practices and navigating the complexities of global agribusiness markets. It proposes that embracing digital transformation and enhancing financial education are pivotal for the future resilience and growth of the agribusiness sector.